PERANAN CREDIT UNION SEBAGAI LEMBAGA PEMBIAYAAN MIKRO Studi Kasus: Pada Usaha UMKM Di Desa Tumbang Manggo Kecamatan Sanaman Mantikei, Kabupaten Katingan, Provinsi Kalimantan Tengah Tahun 2013 - Carollina, Monica; Edi Sutarta, Ag (Modus Journals, 2014)
The role of supporting institutions in the capital in Tumbang Manggu is needed, especially for the small and medium enterprises to obtain loans used for working capital. The main problem that dalam membuka venture capital is limited existence. This study aims to determine the role of Credit Union in TPK Tumbang Manggo, Central Kalimantan as a fnancing institution for micro-enterprises. The data used in this research is secondary data and primary data. Secondary data were obtained f rom the Credit Union TPK Tumbang Manggo and Inkopdit. The primary data obtained through interviews and questionnaires. The analysis used in this research using descriptive analysis. Based on the results of CU not only act as a fnancial institution to assist the public in obtaining funds for venture capital but also as a depository institution money and providers of education and training for their members. It is most infuenced the decision of the respondent in choosing CU as a fnancial institution is the ease in obtaining a loan (20.205%), satisfactory service (20.205%), and ease in obtaining a loan (20.205%). Credits obtained from CU most used by respondents as working capital as much as 80%.Keywords: Credit Union, Credit Union Role, Tings that Afect Decisions, Credit Allocation